The Effect of WAG Ratio and Oil Density on Oil Recovery by Immiscible Water Alternating Gas Flooding - Anuar, Nur Ain Binti Mohd; Yunan, Mat Hussin; Sagala, Farad; Katende, Allan (American Journal of Science and Technology, 2017)
An Enhanced Oil Recovery (EOR) method named Immiscible Water-Alternating-Gas (IWAG) is one of the well-established methods for improving oil recovery in reservoirs. IWAG injection combines both improved displacement efficiency of the gas flooding with an improved macroscopic sweep by water injection. The objective of this study is to investigate the effect of Water-Alternating-Gas (WAG) ratio and oil density on residual oil recovery during IWAG flooding process using dimensions of a real reservoir. A series of six injections were conducted at WAG ratio of 1:1, 1:2, 1:3 and oil densities of 0.72 g/cc, 0.81 g/cc, 0.88 g/cc with flow rate of 1 cc/min for every injection. In this study, a secondary recovery method, which is water-flooding, had been conducted first and continued with immiscible gas-flooding before the start of IWAG to determine the overall recovery factor that can be increased with the utilization of IWAG as an EOR tertiary method. Water flooding had resulted in good oil recovery, which was about 36%–50% Oil Initially In Place (OIIP). Meanwhile immiscible gas-flooding had resulted in only 1% –3% OIIP. The results showed that a WAG ratio of 1:1 was the optimal ratio since the tertiary oil recovery using IWAG was 8% and total 45% of OIIP whereas oil density of 0.72 g/cc was the optimal density which gave 9% of oil recovery using IWAG and total 64% of OIIP. The experimental outcome additionally demonstrated that the IWAG method becomes more efficient in equal water and gas slug ratio which is favourable for low oil density. This is because water and gas help in both microscopic and macroscopic sweep efficiency whereas the mobility of low oil density is higher and flows with low resistance.
Keywords: Enhanced Oil Recovery, Water Alternating Gas, Oil Initial in Place, Viscous Gravity Ratio, Displacement Efficiency, Mobility Ratio